Visually induced motion sickness can be alleviated by pleasant odours - Keshavarz, Behrang; Stelzmann, Daniela; Paillard, Aurore; Hecht, Heiko (Springer, 2015)
Visually induced motion sickness (VIMS) is a common side effect in virtual environments and simulators. Several countermeasures against VIMS exist, but a reliable method to prevent or ease VIMS is unfortunately still miss- ing. In the present study, we tested whether olfactory cues can alleviate VIMS. Sixty-two participants were exposed to a 15-min-long video showing a first-person-view bicycle ride that had successfully induced VIMS in previous studies. Participants were randomly assigned to one of three groups; the first group was exposed to a pleasant odor (rose) while watching the video, the second group was exposed to an unpleasant odor (leather), and the third group was not exposed to any odor. VIMS was measured using a verbal rating scale (0–20) and the Simulator Sickness Questionnaire. Results showed that only half of the participants who were exposed to the odor did notice it (n = 21), whereas the other half failed to detect the odor. However, among those participants who did notice the odor, the rose scent significantly reduced the severity of VIMS compared to the group that did not notice the odor. A moderate positive correlation between odor sensitivity and VIMS showed that participants with higher odor sensitivity also reported stronger VIMS. Our results demonstrate that olfaction can modulate VIMS and that a pleasant odor can potentially reduce VIMS. The relationship between olfactory perception, olfactory sensibility, and VIMS is discussed.